Fake news and fallacies: Exploring vaccine hesitancy in South Africa - Avania Bangalee; Varsha Bangalee (South African Family Practice)
Historically, vaccine hesitancy (VH) has been a thorn in the side of public health efforts to contain and eradicate infectious diseases. This phenomenon is magnified in light of the current coronavirus disease 2019 (COVID-19) pandemic. Surveys conducted across South Africa since the outbreak of COVID-19 demonstrate the complexity of factors that contribute towards VH in this population. Amidst the negative press that the COVID-19 vaccine has received, especially across social media, understanding and combatting VH remains important to achieve herd immunity. This article aims to shed light on key factors fuelling COVID-19 VH in South Africa and provides a framework from which to address this problem.